BUSINESS STRATEGY IN THE ERA OF DISRUPTIVE INNOVATION (DIGITAL ECONOMY) - Nalom Siagian (International Conference on Health Science, Green Economics, Educational Review and Technology, 2019)
The purpose of this article is to explore several original strategic initiatives related to developments in digital business strategies that are currently competing. The focus is on achieving specific strategic goals in business innovation from traditional to digital, or disruptive innovation. The method used in this analysis is a descriptive method with qualitative research techniques. The data analyzed in this paper comes from documents and field facts that occur in the development of the business world in the current digital era, which are then compiled into more detailed data based on several research perspectives. Based on the results of the discussion previously presented, the Era of Disruptive Innovation or the transition from traditional business to digital business is greatly influenced by technological developments and most solutions in business strategies are based on information technology and internet networks. Digital business strategy in the disruption process is defined as activities that aim to find out how business can continue to improve amidst an increasingly rapid digital economy. Strategic priorities in business today can support a business in a strong industry by considering advanced technology and platforms that can be learned and are able to support the business in accordance with its business development goals. Aspects that cannot be separated from business people in carrying out strategies in the current era of disruptive innovation are first, increasing business scope, implementing the latest technological solutions to continue implementing sustainable strategies so that businesses can always compete even in very rapid changes.